KRR sebagai Program Pengembangan Perilaku Seksual Sehat Remaja pada Revolusi Industri 4.0 - Hardi Santosa; Syamsu Yusuf; Ilfiandra Ilfiandra (Universitas Mathla'ul Anwar Banten, 2019)
KRR AS A PROGRAM FOR DEVELOPING HEALTHY SEXUAL BEHAVIOR IN INDUSTRIAL REVOLUTION 4.0. Adolescents are in a transition period characterized by drastic physical changes, psychological instability, and adjustment of new social environments. The era of industrial revolution 4.0, which was marked by the acceleration of information and digitalization of life increasingly added to the challenges of adolescents to be able to achieve the task of sexual development. When adolescents fail to carry out their sexual development tasks, they can have negative implications for adolescent sexual behavior. Understanding and awareness of adolescent reproductive health (KRR) can be an alternative in developing healthy and responsible sexual behavior. This study aims to test KRR as a mode of intervention to develop healthy sexual behavior in adolescents. The research method uses a mixed-method by combining quantitative and qualitative data that supports each other. The research population of tenth-grade high school students was 250 students with a sample of 30 people. Purposive sampling technique by considering the pretest score on the average class is taken into consideration in the selection of samples—data collection by providing a scale of sexual behavior, observation, and interviews. The results of the study show: (1) in general the sexual behavior of students is at a level of caution towards the need for development; (2) The KRR consists of nine guidance content with an audio-visual based group guidance strategy; and (3) the KRR program is effective in developing healthy sexual behavior in adolescents.